Auricular Acupuncture for Pre-Exam Anxiety in Medical Students: A Prospective Observational Pilot Investigation. Issue 2 (April 2016) - Klausenitz, Catharina; Hesse, Thomas; Hacker, Henriette; Hahnenkamp, Klaus; Usichenko, Taras
Objective: Auricular acupuncture (AA) is effective for the treatment of preoperative anxiety. We aimed to study the feasibility and effects of AA on exam anxiety in a prospective observational pilot study. Methods: Healthy medical students received bilateral AA using indwelling fixed needles at points MA-IC1, MA-TF1, MA-SC, MA-AH7, and MA-T on the day before an anatomy exam. The needles were removed after the exam. Anxiety levels were measured using the State-Trait-Anxiety Inventory (STAI) and a 100 mm visual analogue scale (VAS-100) before and after the AA intervention and once again immediately before the exam. The duration of sleep on the night before the exam was recorded and compared to that over the preceding 1 week and 6 months (all through students' recollection). In addition, blood pressure, heart rate and the acceptability of AA to the students were recorded. Results: Ten students (all female) were included in the final analysis. All tolerated the needles well and stated they would wish to receive AA again for exam anxiety in the future. Exam anxiety measured using both STAI and VAS-100 decreased by almost 20% after AA. Conclusions: AA was well accepted, the outcome measurement was feasible, and the results have facilitated the calculation of the sample size for a subsequent randomised controlled trial.